Cephalosporin utilization in the inpatient wards of a teaching hospital in western Nepal - Shankar, P.R.; Subish, P.; Upadhyay, D.; Dubey, A.K.; Deshpande, V.Y. (Journal of Institute of Medicine Nepal, 2007)
Objective and rationale: Information on the utilization of cephalosporins is lacking in hospitals in western Nepal. The present study was carried out to obtain information on the demographic characteristics, cephalosporin prescribing patterns, sensitivity patterns of commonly isolated microorganisms, mean ± SD cost of drugs per patient and the cephalosporin utilization in defined daily dose (DDD)/100 bed-days. Methods: A retrospective analysis of the case records of patients admitted to the inpatient wards of the Manipal Teaching Hospital (a tertiary care hospital in Pokhara, Nepal) and prescribed a cephalosporin during the study period (1.11.2003 to 29.02.2004) was carried out. The median length of stay and cost of the drugs prescribed during the stay was calculated. The frequency of prescribing of other antibiotics co prescribed with cephalosporins was noted. Results: 252 patients (2.56%of total patients) were prescribed cephalosporin. The median length of stay was 9 days. One hundred eighteen patients (46.8%) were prescribed cephalosporin for prophylaxis and 30 patients (11.9%) for bacteriologically proven infections. E .coli, Klebsiella spp., S.aureus, Acinetobacter spp., P.aeruginosa, P. vulgaris and Enterococcus spp. were the common organisms isolated and were generally sensitive to the prescribed cephalosporins.Mean ± SD cost of drugs per hospital admission was 34.78 ± 26.06 US$ and cephalosporins contributed to 51.56%of the total drug costs. Cephalosporin utilization was 4.6 DDDs/100 bed-days. Metronidazole was the most commonly co prescribed. Conclusions: The use of cephalosporins was lower than that reported in the literature. Antibiotic use policies for postoperative prophylaxis and infection control policies for the wards are required. Journal of Institute of Medicine Vol.27(3) 2005